2014
DOI: 10.1371/journal.pone.0102954
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental Factors and Biological Soil Crust Types on Soil Respiration in a Desert Ecosystem

Abstract: The responses of soil respiration to environmental conditions have been studied extensively in various ecosystems. However, little is known about the impacts of temperature and moisture on soils respiration under biological soil crusts. In this study, CO2 efflux from biologically-crusted soils was measured continuously with an automated chamber system in Ningxia, northwest China, from June to October 2012. The highest soil respiration was observed in lichen-crusted soil (0.93±0.43 µmol m−2 s−1) and the lowest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
21
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 38 publications
7
21
0
1
Order By: Relevance
“…Natural vegetation at the site is dominated by Artemisia ordosica (Feng et al, 2014). The site is located at the edge of the Mu Us Desert in the transition between arid and semi-arid climatic zones, at an elevation of 1,550 m a.s.l.…”
Section: Experimental Sitementioning
confidence: 99%
“…Natural vegetation at the site is dominated by Artemisia ordosica (Feng et al, 2014). The site is located at the edge of the Mu Us Desert in the transition between arid and semi-arid climatic zones, at an elevation of 1,550 m a.s.l.…”
Section: Experimental Sitementioning
confidence: 99%
“…Indeed, other than studies focused on Cyanobacteria2324 and a temperature manipulation experiment25, short temporal community dynamics have been neglected. This is surprising given the fact that significant differences in specific desert soil processes have been recorded over the diel (24 hrs) cycle (e.g., CO 2 flux refs 26, 27, 28). In addition, asymmetrical diel warming; i.e., the increase in daily minimum temperature (T min ), is widely observed and set to continue in terrestrial ecosystems2930 and is likely to impact negatively on microbial communities and their processes31.…”
mentioning
confidence: 99%
“…Previous studies demonstrated that soil water content is the predominant source of soil CO 2 flux, due to the impacts of soil moisture in increasing metabolic activity (Feng et al, ; Leon et al, ; Maestre & Cortina, ). Conversely, our results show how a geomorphic disturbance, with local scale variations in the structuring and functioning of landscape, can disturb the soil water content—soil CO 2 flux equation via the occurrence of other regulatory controls at points with higher moisture content.…”
Section: Discussionmentioning
confidence: 99%